Accounting for Waqf Institutions: A Systematic Literature Review on Reporting and Governance Models - Saputra, Wali (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study conducts a Systematic Literature Review (SLR) to explore how waqf institutions manage accounting, financial reporting, and governance. Drawing on 72 peer-reviewed articles published between 2010 and 2024 from Scopus, Web of Science, and ProQuest, this review maps out current practices, emerging trends, and ongoing challenges in waqf financial management. The findings show that many waqf institutions function as hybrid entities, balancing nonprofit goals with commercial activities, which calls for reporting models that can reflect both roles. In Indonesia, PSAK 112 is a key accounting standard for waqf, but its application remains inconsistent, leading to variation in transparency and accountability across institutions. Governance practices—such as internal controls, board supervision, external auditing, and the use of digital transparency tools—play an essential role but are not uniformly implemented. The review also highlights the growing potential of digital platforms and fintech to improve transparency, accountability, and stakeholder engagement. The study concludes by calling for standardized hybrid reporting frameworks, broader adoption of digital governance solutions, and more cross-country empirical research to strengthen the financial sustainability of waqf institutions.